Statistical Optimization of Anti Platelet Drugs in Gastric Floating Tablets Formulation - Akash, Vemuri (International Journal of Pharmaceutical & Biological Archive, 2021)
Floating drug delivery systems (FDDSs) promise to be satisfactory approach for prolonged gastric residence time of drug to improve solubility, lessen drug waste thereby enhances bioavailability (BA) for the drugs that are highly soluble in the lower pH condition. In this present research work, development and evaluation of gastric FDDS of selected three platelet aggregation inhibitors drugs were planned to enhance their BA and/or to minimize their potential side effects with better patient compliance. The three drugs were prasugrel hydrochloride, clopidogrel bisulfate, and dipyridamole which were selected based on their similar physic- chemical characteristics. All these three drugs belong to BCS Class-II (low solubility-high permeability) and exhibit pH-based solubility nature, greater at the lower pH conditions. As per reported literatures, combinational apply of a hydrophobic polymers and hydrophilic polymers well controls initial rapid drug release (DR) of highly soluble drugs. The DR from tablet formulation fabricated by melt granulation employing meltable hydrophobic polymer could be slower due to better uniform and rigid hydrophobic coating around the hydrophilic drug particles. Therefore, in this work, both hydrophilic HPMC K100M (HK100M) and hydrophobic meltable CompritolÂ® 888 ATO (COM888) polymers were chosen in alone and combination to develop and evaluate FDDS of selected three drugs and investigated their individual and combined effects on DR of respective drugs from formulations.